Reirradiation of recurrent glioblastoma: results from a single-center retrospective cohort study - Dejonckheere, Cas S.; Zeyen, Thomas; Duffy, Cathrina; Layer, Yannik C.; Potthoff, Anna-Laura; Wichtmann, Barbara D.; Friker, Lea L.; Scafa, Davide; Leitzen, Christina; Nour, Younèss; Kugel, Fabian; Schäfer, Niklas; et al. (Clinical and translational radiation oncology, 2025)
Purpose - The management of recurrent glioblastoma (rGBM) remains a clinical challenge, with only limited therapeutic options available to date. Reirradiation may offer a progression-free survival (PFS) benefit in selected cases, but data are scarce. - Methods - Consecutive patients from the last 10 years with GBM (CNS WHO grade 4, IDH-wildtype) who underwent at least one additional course of cranial radiotherapy for suspected or histopathologically confirmed rGBM at a tertiary neuro-oncological center were retrospectively analyzed. The primary endpoint was PFS, secondary endpoints included reirradiation-related adverse event rates, with a particular focus on radiation necrosis (RN). - Results - Fifty-nine patients were included with a median follow-up (range) of 8.7 (0.5-48.0) months after reirradiation. The median time to first recurrence was 15 (4-89) months, with the majority occurring in-field (59.7 %). The EQD2⍺/β=10 ranged from 31.3-80.2 Gy with a median prescription dose of 42 Gy. Reirradiation was combined with systemic therapy in 81.4 % of patients. No grade 3-5 acute reirradiation-related adverse events were observed. RN was diagnosed in 16.9 % of patients (80 % grade 2 and 20 % grade 3), with a notably low rate in those receiving anti-VEGF therapy parallel to reirradiation. RN risk was independent of reirradiation volume or dose (p = 0.15 and 0.43, respectively). The disease control rate following reirradiation was 83.6 % and the median PFS was 5.9 (0.5-48.0) months. Concomitant chemotherapy or anti-VEGF therapy was significantly associated with improved outcomes (p = 0.049), whereas smaller reirradiation volumes demonstrated a non-significant trend towards longer PFS (p = 0.23). - Conclusion - In this retrospective analysis, reirradiation for rGBM was feasible and safe, conferring a potential PFS benefit in selected patients. Bevacizumab emerged as a particularly promising combination partner, contributing to both RN prevention and enhanced efficacy.